Trends and Outcomes of Transcatheter Aortic Valve Implantation (TAVI) in Korea: the Results of the First Cohort of Korean TAVI Registry - Yu, Cheol Woong; Kim, Won-Jang; Ahn, Jung-Min; Kook, Hyungdon; Kang, Se Hun; Han, Jung-Kyu; Ko, Young-Guk; Choi, Seung-Hyuk; Koo, Bon-Kwon; Chang, Kiyuk; Kim, Hyo-Soo (Korean circulation journal, 2018)
There has been no nation-wide data on the outcomes of transcatheter aortic valve implantation (TAVI) after commercialization of TAVI in Korea. We report clinical features and outcomes of the first cohort of TAVI performed from Jun 2015 to Jun 2017 in Korea. The first cohort of Korean-TAVI (K-TAVI) registry includes 576 consecutive patients with severe symptomatic aortic stenosis who underwent TAVI from 17 Korean hospitals for 2 years. Most of TAVI procedures were performed for septuagenarians and octogenarians (90.8%) through transfemoral approach (98.3%). The rate of device success was 92.5% and permanent pacemaker was implanted in 5.6%. In successive years, incidences of paravalvular leakage (PVL) and major bleeding declined. Society of Thoracic Surgeons (STS) score was 5.2 (3.0 to 9.0) and 34.7% of patients had high surgical risk (STS ≥8). One-year all-cause death occurred in 8.9% and was significantly lower in low to intermediate risk one than in high risk (5.4% vs. 15.5%, p<0.001). The independent predictors of 1-year mortality were age (hazard ratio [HR], 1.087; 95% confidence interval [CI], 1.036-1.141; p=0.001), moderate or severe PVL (HR, 4.631; 95% CI, 1.624-13.203; p=0.004) and end-stage renal disease (HR, 5.785; 95% CI, 2.717-12.316; p<0.001). K-TAVI registry showed favorable 1-year outcomes with decreasing complication rate over time in real-world Korean patients. Two-thirds of patients were low to intermediate surgical risk and showed a significantly lower mortality than the high-risk patients, suggesting the promising future on the expanded indications of TAVI.